DIGITAL ERA ENTREPRENEURSHIP AND THE DEVELOPMENT OF NEW ENERGY VEHICLES IN EMERGING MARKET - Liza Amalia Putri; Qing Sun (Jurnal Ilmiah Publipreneur, 2026)
The rapid development of digital technologies has significantly transformed entrepreneurial ecosystems worldwide, fostering innovation across industries, including transportation. One of the most notable advancements is the emergence of New Energy Vehicles (NEVs), which integrate environmental sustainability with digital innovation. This study examines the role of digital entrepreneurship in driving the development of NEVs in emerging markets, with a particular focus on Indonesia. Using a qualitative descriptive approach based on secondary data, this research identifies key opportunities such as digital platform integration, government incentives, and increased environmental awareness. At the same time, it highlights persistent challenges, including high capital requirements, limited infrastructure, and technological complexity. The findings emphasize the importance of collaboration among entrepreneurs, policymakers, and educational institutions in developing a sustainable NEV ecosystem. This study contributes to the field of digital entrepreneurship within the creative and applied industry focus of Polimedia.